Comparative evaluation of apical extrusion of intracanal bacteria using four single-file NiTi instruments: An in vitro study - A Sheerin Sarthaj; V Rajesh Gopal; A Arvind Kumar; Benin Paulaian; Lal Krishnan Raveendran; C S DeviPrasad (Wolters Kluwer Medknow Publications, 2019)
Introduction: A major objective in root canal treatment is to clean the root canal system. During the process, dentine chips, pulp tissue fragments, necrotic tissue, microorganisms, and intracanal irrigants may be extruded through the apical foramen. This in vitro study was conducted to evaluate the apical extrusion of Enterococcus faecalis with One Shape, F360, WaveOne, and Reciproc endodontic single-file systems. Materials and Methods: Seventy-five human single-rooted mandibular premolar teeth were selected. Endodontic access cavities were prepared. Pulp chamber was accessed, and a pure culture of E. faecalis was used to infect the root canals. Vials with rubber stoppers were selected as the test apparatus. Then, the samples were broadly divided into four main groups with a sample size of 15 teeth. Fifteen previously infected teeth were used as controls. All the root canals were instrumented with the size 25 instruments. A total volume of 2 ml of saline was used for each root canal as irrigant. After 24 h, colonies of bacteria were counted using classical bacterial counting technique as colony-forming units. Statistical Analysis: Data were analyzed statistically using Statistical Package for the Social Sciences, version - 21 (IBM Corp., NY) Software for Windows. Data were expressed in its mean and standard deviation. Results: The results indicated that all the four single-file systems tested caused a measurable apical extrusion of debris. Statistically, significant difference was observed between One Shape, F360, WaveOne, and Reciproc in terms of E. faecalis extrusion, P < 0.05. The highest mean value was with One Shape rotary single-file system and the lowest mean value was with WaveOne reciprocating single-file systems. Conclusion: Within the limitations of the present study, it can be concluded that the reciprocating single-file systems extruded less amount of E. faecalis than compared to rotary single-file systems.